Feminisation of poverty in 12 welfare states: strengthening cross-regime variations? - Kim, Jin Wook; Choi, Young Jun (Luxembourg, 2010)
"The feminisation of poverty is said to have become a common feature in the majority of advanced welfare states, but it is equally true that there has been significant variation in the feminisation of poverty from one country to another. While the concept of the feminisation of poverty remains controversial, there have been very few attempts to reveal a detailed picture from a comparative perspective. Considering this background, this study aims to illustrate the feminisation of poverty in 12 welfare states (Liberal ? Australia, Canada, UK, US; Conservative ? Austria, France, Germany, Italy; Nordic ? Denmark, Finland, Norway, Sweden) between the 1980s and the 2000s and to analyse whether or not there has been any convergence or divergence between these welfare states. This study will evaluate the scope and depth of the feminisation of poverty by conducting analyses not only in terms of different sex, but in terms of different population groups. Further, the changing role of welfare states will be assessed via an analysis of the antipoverty role of public transfers in each country. The Luxemburg Income Study dataset will be used for empirical analysis. This paper will argue that while the feminisation of poverty has been slowed down and even reversed in certain cases, cross-national differences have been increasingly visible. The results of this study also show that the welfare regime framework can prove to be a useful tool for understanding the similarities and the differences in the feminisation of poverty across different Western welfare state regimes."